Improving outcomes for patients with relapsed multiple myeloma: Challenges and considerations of current and emerging treatment options. (September 2021) - Ramasamy, Karthik; Gay, Francesca; Weisel, Katja; Zweegman, Sonja; Mateos, Maria Victoria; Richardson, Paul
Abstract: Despite the recent introduction of new therapies for multiple myeloma (MM), it remains an incurable disease. As MM progresses, patients experience cycles of relapse and remission, with remission periods becoming increasingly shorter as the disease becomes less treatment-sensitive. The treatment of relapsed refractory MM (RRMM) remains a significant clinical challenge. Patients with RRMM are a highly heterogeneous group and choosing the most appropriate treatment requires careful consideration. Furthermore, the number of treatment options for MM is continually growing with no definitive consensus to guide treating clinicians. The emergence of second-generation proteasome inhibitors (e.g., carfilzomib and ixazomib), immunomodulatory drugs (e.g., pomalidomide) and monoclonal antibodies (e.g., isatuximab) has expanded an already complex treatment landscape. This review provides a clear summary of the available treatments for MM and discusses how to tailor treatments to individual patients' needs. Novel treatments currently under clinical development, including venetoclax, melflufen and CAR T-cell therapies, are also discussed.